New African Cinema - Orlando, Valerie, 1963- (Book collections on Project MUSE., 2017)
New African Cinema examines the pressing social, cultural, economic, and historical issues explored by African filmmakers in the new millennium by offering an overview of the development of postcolonial African cinema as it has evolved since the 1960s into the new medium, known as ""new African cinema, "" it is today.